Perencanaan Jadwal Induk Produksi pada Produk Nas Shoes dengan Menggunakan Metode Perencanaan Agregat di Perusahaan Furniture - Anisya Kusumaningrum; Renanda Nia Rachmadita; Rina Sandora (Proceedings Conference On Design Manufacture Engineering And Its Application, 2018)
In furniture companies in general, which produces a variety of products including nasshoes, tenma, fukai, woodone . Nowadays the company is faced with the problem of congestion on a kind of product and experiencing deficiencies in other products because this furniture companies using production scheduling based on experience demand in the previous period. To solve this problem the company needs to establish a good Master Production Planning to balance production capacity with its own resources so as to achieve minimal cost. The purpose of this study is to determine the appropriate aggregate planning so as to obtain the optimal cost. In this study used Aggregate Planning Methods to achieve optimal production cost. First steps to make the master production schedule is calculation of forecasting using linear regression, moving average, and exponential smooting and then calculation of production cost with three aggregat planning methods of transportation method, permanent labor method and trial and error method. From the calculation master production planning using aggregate planning method with three alternative that is transportation, permanent labor and last trial and error, so that obtained optimal result there is at alternative transportation with production cost as $120.892,10 and the reduction cost as big as $137,90 and total production equal to 2626 units for 6 month.